Dual‐function interface engineering for efficient perovskite solar cells. Issue 2 (18th February 2021) - Luan, Yigang; Wang, Fuhui; Zhuang, Jing; Lin, Tao; Wei, Yuanzhi; Chen, Ningli; Zhang, Yanyan; Wang, Fuyi; Yu, Ping; Mao, Lanqun; Liu, Huibiao; Wang, Jizheng
Abstract: Interface engineering has been proven a powerful tool to improve performances of the perovskite solar cells (PSCs). Herein, highly π‐conjugated graphdiyne (GDY) is employed as an interface linker between the perovskite film and the hole transport layer (HTL). It is found that GDY can significantly suppress the formation of metallic Pb (a detrimental defect), and reduces carrier recombination. The linker can also form π‐π stacking interaction with the HTL, and facilitates transport and collection of photogenerated holes. The perovskite/GDY/HTL combination leads to large improvement in both power conversion efficiency (from 19.94% to 22.17%) and device stability. In addition, the GDY is also applied to the 3D/2D PSCs, and an outstanding PCE of 23.42% is achieved. Abstract : Highly π‐conjugated graphdiyne is demonstrated to be an effective dual‐function linker in PSCs, which can not only reduce metallic Pb defects but also interact with hole transporter Spiro‐OMeTAD. The application of graphdiyne to the 3D/2D PSCs leads to an outstanding PCE of 23.42%.